Impact of using Telehealth to Improve Maternal Outcomes During Pandemic Covid-19 - Amel Dawod Kamel Gudia; Noura Mohamed El Toukhi (Global Health Science Group, 2020)
Implementation of telehealth and telehealth during COVID-19 pandemic have become crucial to ensure the safe antenatal and delivery A developing country with relatively high maternal mortality number. One of the influencing factors for that condition is health services at antenatal, intranatal postnatal period and during women life span has not been optimized yet. The optimization effort has been done in several countries through health service based on utilization of technology. The literature study aimed to effect Tele health implementation in the maternity nursing care. The implementation of Tele health in maternity nursing care showed positive impact in knowledge, motivation, and health behavior of the mother. developing country which can be strategic to utilizing tele-nursing support that help in reducing the Maternal Mortality Rate. Telehealth may provide a solution for maintaining continuity of care while practicing physical distancing. COVID-19 has prompted new temporary telehealth flexibilities, expanding access to care through virtual means. These new flexibilities provide an opportunity to expand access to pregnancy and childbirth services and may help to mitigate adverse health outcomes for pregnant women.